IoT Based Health Monitoring for Heart Rate and Body Temperature - Mazelam, Muhammad Faiz; Zulkifli, Shamsul Aizam (Evolution in Electrical and Electronic Engineering, 2023)
In this era of modernization, most companies compete among themselves to follow the standard and systems that meet the technology currently used. Data collection using papers having issues for current health monitoring situation where the increases of population and growth in rural and cities areas. Communication between machines of systems needed to be monitored using the Internet of Things (IoT) platform. A continuous power supply will be needed as the system will be updated every second. The method of this project will be the implementation of health monitoring based on IoT. DC-DC Buck Converter will be designed as a continuous power supply for the system development. The solution for the internet connection will be the use of a microcontroller with a WIFI (wireless fidelity) module that is NodeMcu. The parameter for this project will be the reading of the heart rate from the AD8232 heart rate sensor and body temperature from the DS18B20 temperature sensor that will display on the IoT platform. The Pulse Width Modulation (PWM) from the Arduino microcontroller will operate based on the duty cycle that is programmed. This project can display the analog heartbeat and body temperature that is almost the same as the actual body temperature of the user doing the cardiovascular exercise. This project also can have the heart rate reading in BPM (beat per minute) using the formula. Therefore, IoT-based health monitoring for heart rate and body temperature can be developed with a continuous power supply to have real-time and continuous data stored on an IoT platform.